IMPLEMENTASI AKAD AL-IJARAH AL-MAUSHUFAH FI AL-DZIMMAH SEBAGAI ALTERNATIF PEMBIAYAAN DI LEMBAGA KEUANGAN SYARIAH INDONESIA - Fuadi, Nasrul Fahmi Zaki (UIN Raden Mas Said Surakarta, 2019)
The development of Sharia Banking in Indonesia has increased quite well, both from Assets, Third Party Funds (DPK), and Distributed Financing (PYD). Developments are caused by joint efforts to develop Islamic Banking in Indonesia. This can be seen from the commitment of the Indonesian Ulema Council (MUI) in guarding from the side of the availability of fatwa. One example of his fatwa is the DSN-MUI Fatwa NO: 101 / DSN-MUI / X / 2016 Tentang 101-Akad Al-Ijarah Al-Maushufah Fi Al-Dzimmah. But in practice, the contract used in Islamic Banking is still dominated by murabahah contracts. So the researcher feels it is important to examine how the role and implementation of the contract in products and services in Islamic banking. The researcher also discussed how the fiqh study of muamalah was about the al-Ijarah al-Maushufah Fi al-Dzimmah contract.